Challenge of the nineties: earning our way through production: statement to Parliament - Patterson, P.J. (Jamaica Information Service KingstonJA, 1990)
Consequent to the new programme which Jamaica entered into with the International Monetary Fund on 30 January 1990, this statement deals with the companion measures to stimulate production and growth.